МНОГОМЕРНАЯ ГРАНИЧНАЯ ТЕОРЕМА МОРЕРА В КЛАССИЧЕСКОЙ ОБЛАСТИ ЧЕТВЕРТОГО ТИПА - Отемуратов, Б.П.; Халкназаров, А.М.; Кутлымуратов, Б.Ж. (SCIENCE and SOCIETY, 2023)
In this article, boundary variants of Morera’s theorem for classical domains of the fourth types are obtained